Giant Pericardial Cyst - Eroding Left Ventricle - Shah, Ram Kishor; Jaiswal, RK; Pokharel, DP (Nepalese Heart Journal, 2017)
Pericardial cyst is the result of an outpuching of the parietal pericardium that is lined by mesothelial cells. They represent 6% of mediastinal masses, and 33% of mediastinal cysts. Other cysts in the mediastinum are brochogenic-34%, enteric-12%, thymic and others-21%. A 19 year old man admitted with exertional breathlessness and a typical chest pain. The result of physical examination was within normal linits. Resting 12-lead electrocardiography shows T inversion in lead 1, AVL, V5 and V6. A posteroanterior chest radiograph revealed a cystic mass in the mediastinum. Transthoracic and transoesophageal echocardiography confirmed the presence of a large fluid filled cyst within the pericardial space. Contrast CT imaging revealed a giant pericardial cyst (10x10x12cm) in left cardiophrenic angle, later confirmed intraoperatively and by histopathology. Pericardial cysts occur at the rate of 1 person per 100,000. Seventy five percent of them have no associated symptoms, and are usually found incidentally during routine chest x-ray or echocardiography. Cardiac tamponade, obstruction of right main stem bronchus, and sudden death are the life threatening emergencies that have been reported. The management of pericardial cysts includes observation, percutaneous drain-age, and resection.